Job Stress, Work Life Balance, and Workplace Wellbeing : A Bibliometric Analysis - Errica Dwitanti; Madziatul Churiyah (CV. Syntax Corporation Indonesia, 2022)
Correlational research is a research that includes data collection activities selecting and determining between the relationship and the degree of relationship between two or more variables. The existence of relationships and the level of variables is very important because by knowing more about the level of existing relationships, researchers can provide explanations according to the research objectives, namely research that is used as hypothesis testing or theory that is useful for strengthening hypotheses or theories or rejecting hypotheses that have been studied previously. Quantitative research with a descriptive approach will turn into hypothesis testing (hypothesis testing) or explanatory research (explanatory research).